Peran Ekspor, Nilai Tukar dan Suku Bunga Terhadap Jumlah Cadangan Devisa di Indonesia - Fachru Nofrian fachru; Baihaqi Alfathony baihaqi (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The limited amount of foreign exchange reserves owned by Indonesia is still one of the problems faced today. Foreign exchange reserves will also continue to change due to macroeconomic factors such as exports, exchange rates and interest rates. This study aims to determine the role of exports, exchange rates and interest rates on the amount of foreign exchange reserves in Indonesia. This research uses multiple linear regression with the Ordinary Least Square (OLS) method and quantitative descriptive analysis. The data used is secondary data with time series from 1988-2020 with a total of 33 observations. The data is processed using eviews 10 software. The results of this study indicate that partially (1) exports have a significant positive effect on the amount of foreign exchange reserves in Indonesia (2) the exchange rate has a significant positive effect on the amount of foreign exchange reserves in Indonesia (3) the interest rate has a significant negative effect on the amount of foreign exchange reserves in Indonesia, while simultaneously or simultaneously exports, exchange rates and interest rates affect the amount of foreign exchange reserves in Indonesia.